2018
DOI: 10.5194/acp-18-7509-2018
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying errors in surface ozone predictions associated with clouds over the CONUS: a WRF-Chem modeling study using satellite cloud retrievals

Abstract: Abstract. Clouds play a key role in radiation and hence O 3 photochemistry by modulating photolysis rates and lightdependent emissions of biogenic volatile organic compounds (BVOCs). It is not well known, however, how much error in O 3 predictions can be directly attributed to error in cloud predictions. This study applies the Weather Research and Forecasting with Chemistry (WRF-Chem) model at 12 km horizontal resolution with the Morrison microphysics and Grell 3-D cumulus parameterization to quantify uncertai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 47 publications
6
32
0
Order By: Relevance
“…Journal of Geophysical Research: Atmospheres 3.1.4. Cloud Coverage Clouds are known to influence ozone concentrations directly by modulating photolysis (Ryu et al, 2018). Furthermore, they can influence ozone concentrations indirectly through lightning NO x (Hauglustaine et al, 2001) and by changing biogenic VOC emissions via shifts in radiation and temperature (Ryu et al, 2018).…”
Section: 1029/2019jd031971mentioning
confidence: 99%
See 1 more Smart Citation
“…Journal of Geophysical Research: Atmospheres 3.1.4. Cloud Coverage Clouds are known to influence ozone concentrations directly by modulating photolysis (Ryu et al, 2018). Furthermore, they can influence ozone concentrations indirectly through lightning NO x (Hauglustaine et al, 2001) and by changing biogenic VOC emissions via shifts in radiation and temperature (Ryu et al, 2018).…”
Section: 1029/2019jd031971mentioning
confidence: 99%
“…Cloud Coverage Clouds are known to influence ozone concentrations directly by modulating photolysis (Ryu et al, 2018). Furthermore, they can influence ozone concentrations indirectly through lightning NO x (Hauglustaine et al, 2001) and by changing biogenic VOC emissions via shifts in radiation and temperature (Ryu et al, 2018). Errors in WRF-Chem cloud fields were found by Ryu et al (2018) to propagate to changes in average MDA8 ozone by 1-5 ppb over Contiguous United States (CONUS).…”
Section: 1029/2019jd031971mentioning
confidence: 99%
“…Model bias in surface ozone is a good indicator that the budgets and processing of nitrogen oxides (NO x ) or volatile organic compounds (VOCs) are poorly constrained. Past studies have suggested different solutions including the need for updates to model representation of clouds (Ryu et al, 2018), emissions of NO (Travis et al, 2016;McDonald et al, 2018b) or biogenic hydrocarbons (Kaiser et al, 2018), chemistry (Squire et al, 2015), chemical solver (Sun et al, 2017), and deposition (Val Martin et al, 2014;Clifton et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The Henry's law and isoprene updates do not change ozone much above the surface while the terpene updates do reduce ozone in the PBL. The vertical profile shapes for ozone, NO, isoprene, and monoterpenes are quite different between the model and observations suggesting that updates to the PBL height, mixing schemes, clouds (Ryu et al, 2018), vertical resolution, or ozone dry deposition schemes (Clifton et al, 2019) may be needed to further reduce ozone biases in CESM/CAM-chem.…”
mentioning
confidence: 90%
“…model and observations for NO 2 photolysis because field campaigns typically avoid sampling clouds on a scale not resolved by the model (Hall et al, 2018). In Ryu et al (2018), WRF-chem similar to CAM-chem under-predicts NO photolysis above 2 km and when clouds derived from satellites are incorporated into WRF-chem the NO 2 photolysis bias is removed and MDA8 surface ozone decreases by 1 to 5 ppb. Additionally, studies using large eddy simulations have determined that shallow cumulus clouds enhance vertical transport of passive (i.e., no aqueous-phase processing) chemical compounds as compared to clear sky conditions (Vila-Guerau de Arellano et al, 2005;Li et al, 2017).…”
mentioning
confidence: 99%